SURGICAL MANAGEMENT OF HYDROCEPHALUS – MODERN TECHNIQUES AND LONG-TERM OUTCOMES - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Surgical treatment remains the cornerstone of hydrocephalus management. Over the past decades, significant progress has been made in shunt technology and endoscopic procedures. This article discusses current surgical techniques, perioperative care, and long-term outcomes in patients with hydrocephalus.